2016
DOI: 10.5665/sleep.5342
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia, Nightmares, and Chronotype as Markers of Risk for Severe Mental Illness: Results from a Student Population

Abstract: Insomnia, nightmares, and circadian phase delay are associated with increased subsyndromal psychiatric symptoms in young people. Each is a treatable sleep disorder and might be a target for early intervention to modify the subsequent progression of psychiatric disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 45 publications
7
105
1
2
Order By: Relevance
“…Indeed, our post-hoc regression analysis further confirmed that sleep quality was not a significant predictor of paranoia. This is surprising as several studies have reported links between a range of sleep disturbances and paranoia (Kahn-Greene et al, 2007;Sheaves et al, 2016;Reeve et al, 2017).…”
Section: Sleep Quality and Paranoiamentioning
confidence: 91%
See 2 more Smart Citations
“…Indeed, our post-hoc regression analysis further confirmed that sleep quality was not a significant predictor of paranoia. This is surprising as several studies have reported links between a range of sleep disturbances and paranoia (Kahn-Greene et al, 2007;Sheaves et al, 2016;Reeve et al, 2017).…”
Section: Sleep Quality and Paranoiamentioning
confidence: 91%
“…Another study administered the Oxford Sleep Survey which includes questions on sleep and psychotic like experiences (PLE's) to over 1000 students. Results found links between a number of sleep disorder symptoms such as insomnia, nightmare frequency and nightmare distress and PLE's including paranoia (Sheaves et al, 2016). In a large -scale general population study conducted of 8580 people, there were strong relationships between insomnia and paranoia.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although sleep disturbances are known to affect health and behavior, 6 we cannot presume a direct causal relationship between such outcomes and SJL, which appears mostly as a variable that characterizes the study samples. Thus, we chose to exclude studies that did not explicitly assess illness Levandovski et al 2011 29 Roenneberg et al 2012 21 Johnsen et al 2013 22 Kantermann et al 2013 27 Schimitt et al 2013 35 Haraszti et al 2014 40 Kantermann et al 2014 25 Miller et al 2015 44 Rutters et al 2014 28 Borisenkov et al 2015 32 Parsons et al 2015 35 Tavernier et al 2015 42 Wong et al 2015 26 Choi et al 2016 45 Kolomeichuk et al 2016 38 Polugrudov et al 2016 24 Sheaves et al 2016 30 Silva et al 2016 46 Yong states or behavioral outcomes. Furthermore, it is very likely that sleep deficit correlates with SJL.…”
Section: Excluded Studies and Terminologymentioning
confidence: 99%
“…However, no association was found in young students aged between 12 and 21 years 12 or in undergraduate students of median age of 21 years. 30 Depressive symptoms in young individuals may be associated with factors other than circadian misalignment (eg, puberty, hormones, sexual or emotional abuse). The associations of SJL with such outcomes might appear at the beginning of the adult life, when chronotypes tend to be the latest and, consequently, SJL is at its highest.…”
mentioning
confidence: 99%